Decentralisation and forest management in Kapuas district, Central Kalimantan - McCarthy, J.F. (Center for International Forestry Research, 2001)
This case study discusses decentralisation and forest management in Kapuas district, Central Kalimantan, focusing specifically on the impact of these administrative reforms on timber concessions operating there. It is based on field research carried out during June and July 2000. The study is based on interviews with government officials, forestry department staff, university researchers, NGO workers and the employees of timber workers in the provincial capital, Palangkaraya, and the district capital, Kuala Kapuas. Research was also carried out in Gunung Mas in the headwaters of the Kahayan River and further interviews were conducted with businessmen, sub-district government officials and lower level forestry staff, community leaders and local villagers. This document provides: (1) Essential background regarding the geography, economy and history of forestry in Kapuas district. (2) A discussion focuses on decentralisation and forest management, analysing the financial situation of the district administration, the efforts of the district government to create district laws to regulate the forestry sector in the district, and the initial impacts of decentralisation on spatial planning and environmental management. (3) Analyses the situation of timber concessionaires in Gunung Mas just before the decentralisation laws took effect, focusing on the changing relationships among timber companies, the local administration and local communities. The case study examines the endemic conflicts occurring between local communities and logging concessionaires in the area. Finally, it draws some conclusions regarding the impact of decentralisation on forest management in the district.